'Brazil after Bolsonaro: The comeback of Lula da Silva' - Sven da Silva (European Review of Latin American and Caribbean Studies)
Brazil after Bolsonaro: The comeback of Lula da Silva, edited by Richard Bourne, Routledge, 2024